Electrochromic device, method of manufacturing same, and window device including same
Patent Information
- Application Number
- KR1020250038148
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-03-25
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-03-25
Smart Images

Figure 112025033863712-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The embodiments relate to an electrochromic element, a method for manufacturing the same, and a window device including the same. Background Technology
[0002] Electrochromic films are films in which color changes due to oxidation-reduction reactions at respective oxidation and reduction electrodes caused by an applied potential, and are films in which the user can artificially control visible light and infrared light, and various types of inorganic oxides are used as electrode materials.
[0003] As described above, various electrochromic films have been developed and patented. Examining the patent applications, Korean Published Patent Application No. 특2001-0087586 describes a film in which a conductive indium-tin oxide thin film is deposited on a glass film, and among two ITO films (1A, 1B), a reducing chromogenic oxide MoO3 is deposited on one and a reducing chromogenic material WO3 is deposited on the other, followed by the deposition of a lithium-based solid electrolyte, an alkali metal, on top, and a conductive polymer polyaniline is placed between the two films. The film changes from transparent to blue when voltage is applied by passing it through a high-frequency compression roller. Additionally, Korean Registered Utility Model Publication No. 0184841 describes a transition metal oxide in which indium-tin oxide is deposited on a 0.05 mm thick glass film, and then a reducing chromogenic material WO3 and an oxidizing chromogenic material IrO2 are deposited with an α-PEO copolymer, a polymer solid electrolyte, in between. An electric energy-induced color-changing film is known, characterized by being bonded to both sides of the film with high-frequency rollers. The problem to be solved
[0004] The embodiments aim to provide an electrochromic element having improved durability and discoloration speed, a method for manufacturing the same, and a window device including the same. means of solving the problem
[0005] An electrochromic element according to an embodiment comprises: a first substrate; a first transparent electrode disposed on the first substrate; a first color-changing layer disposed on the first transparent electrode; an electrolyte layer disposed on the first color-changing layer; a second color-changing layer disposed on the electrolyte layer; a second transparent electrode disposed on the second color-changing layer; a second substrate disposed on the second transparent electrode; and a lithium-rich layer disposed adjacently below the second color-changing layer and containing lithium at a higher concentration than the second color-changing layer.
[0006] In an electrochromic element according to one embodiment, the concentration of lithium in the second chromic layer may become progressively smaller as it approaches the second transparent electrode from the lithium-rich layer.
[0007] In an electrochromic element according to one embodiment, the lithium-rich layer may include lithium hydroxide.
[0008] In an electrochromic element according to one embodiment, the first substrate and the second substrate may be flexible.
[0009] In an electrochromic device according to one embodiment, the lithium-rich layer may have a thickness of 10 nm to 1000 nm.
[0010] In an electrochromic element according to one embodiment, the first chromogenic layer may comprise tungsten oxide, and the second chromogenic layer may comprise nickel oxide.
[0011] In an electrochromic element according to one embodiment, the lithium-rich layer may contain lithium at a higher concentration than the electrolyte layer.
[0012] A method for manufacturing an electrochromic device according to an embodiment comprises the steps of: preparing a first laminate including a first substrate, a first transparent electrode on the first substrate, and a first color-changing layer on the first transparent electrode; preparing a second laminate including a second substrate, a second transparent electrode on the second substrate, a second color-changing layer on the second transparent electrode, and a lithium-rich layer on the second color-changing layer; and bonding the first laminate and the second laminate through an electrolyte layer, wherein the lithium-rich layer contains lithium at a higher concentration than the second color-changing layer.
[0013] In a method for manufacturing an electrochromic device according to one embodiment, the step of preparing the second laminate may include the step of coating a lithium hydrate on the second chromogenic layer.
[0014] In a method for manufacturing an electrochromic device according to one embodiment, the step of preparing the second laminate may further include the step of heat-treating the lithium hydrate.
[0015] In a method for manufacturing an electrochromic device according to one embodiment, the concentration of lithium in the second chromic layer may become progressively smaller as it approaches the second transparent electrode from the lithium-rich layer.
[0016] A window device according to an embodiment includes a frame; a window mounted on the frame; and an electrochromic element disposed in the window, wherein the electrochromic element includes a first substrate; a first transparent electrode disposed on the first substrate; a first color-changing layer disposed on the first transparent electrode; an electrolyte layer disposed on the first color-changing layer; a second color-changing layer disposed on the electrolyte layer; a second transparent electrode disposed on the second color-changing layer; a second substrate disposed on the second transparent electrode; and a lithium-rich layer disposed adjacent to the second color-changing layer and containing lithium at a higher concentration than the second color-changing layer. Effects of the invention
[0017] The electrochromic element according to the embodiment has a lithium-rich layer. Accordingly, the electrochromic element according to the embodiment can improve the movement speed of lithium ions during the driving process. That is, the lithium-rich layer can supply lithium ions to the second chromic layer at a high speed, thereby changing the color of the second chromic layer.
[0018] In addition, the second color-changing layer may have an increasingly higher lithium concentration as it approaches the lithium-rich layer. Accordingly, the electrochromic device according to the embodiment can improve the color-changing speed in the early stages of color change.
[0019] In addition, since the second color-changing layer is adjacent to the lithium-rich layer, it can contain lithium ions at a high concentration. That is, the second color-changing layer can accommodate lithium ions at a high concentration.
[0020] In addition, since the second color-changing layer is adjacent to the lithium-rich layer, it can receive a high concentration of lithium ions. Accordingly, the second color-changing layer can rapidly accommodate a high concentration of lithium ions.
[0021] Accordingly, the second color-changing layer can change color at a rapid rate to have an appropriate color and appropriate transmittance.
[0022] Accordingly, the electrochromic element according to the embodiment can have improved color change speed and color change performance.
[0023] In addition, since the lithium contained in the lithium-rich layer gradually diffuses into the second color-changing layer, the electrochromic element according to the embodiment can easily color and decolorize the second color-changing layer.
[0024] Accordingly, the electrochromic element according to the embodiment can reduce the chemical shock applied to the second color-changing layer during the coloring and / or decolorization process.
[0025] Accordingly, the electrochromic element according to the embodiment can reduce operating time, reduce discoloration shock, and have improved durability. Brief explanation of the drawing
[0026] FIG. 1 is a cross-sectional view illustrating one cross-section of an electrochromic element according to an embodiment. FIGS. 2 to 5 are drawings illustrating the process of manufacturing an electrochromic element according to an embodiment. FIG. 6 is a drawing illustrating a window device according to an embodiment. Specific details for implementing the invention
[0027] In the description of the embodiments, where each part, surface, layer, or substrate, etc. is described as being formed "on" or "under" each part, surface, layer, or substrate, etc., "on" and "under" include both being formed "directly" and "indirectly" through other components. Furthermore, the reference for the "on" or "under" of each component is explained based on the drawings. The size of each component in the drawings may be exaggerated for illustrative purposes and does not represent the actual size applied.
[0028] FIG. 1 is a cross-sectional view illustrating one cross-section of an electrochromic element according to an embodiment.
[0029] Referring to FIG. 1, an electrochromic element according to an embodiment includes a first substrate (100), a second substrate (200), a first transparent electrode (300), a second transparent electrode (400), a first color-changing layer (500), a second color-changing layer (600), a lithium-rich layer (700), and an electrolyte layer (800).
[0030] The first substrate (100) supports the first transparent electrode (300), the first color-changing layer (500), the second color-changing layer (600), the second transparent electrode (400), the lithium-rich layer (700), and the electrolyte layer (800) together with the second substrate (200).
[0031] Additionally, the first substrate (100) sandwiches the first transparent electrode (300), the first color-changing layer (500), the second color-changing layer (600), the lithium-rich layer (700), the second transparent electrode (400), and the electrolyte layer (800) together with the second substrate (200). The first substrate (100) can protect the first transparent electrode (300), the first color-changing layer (500), the second color-changing layer (600), the second transparent electrode (400), the lithium-rich layer (700), and the electrolyte layer (800) from external physical and chemical shocks together with the second substrate (200).
[0032] The first substrate (100) may include a polymer resin. The first substrate (100) may include at least one from the group consisting of a polyester resin, a polyimide resin, a cyclic olefin polymer resin, a polyethersulfone, a polycarbonate, or a polyolefin resin.
[0033] The first substrate (100) may include a polyester resin as a main component. The first substrate (100) may include polyethylene terephthalate. The first substrate (100) may include the polyethylene terephthalate in an amount of about 90 wt% or more based on the total composition. The first substrate (100) may include the polyethylene terephthalate in an amount of about 95 wt% or more based on the total composition. The first substrate (100) may include the polyethylene terephthalate in an amount of about 97 wt% or more based on the total composition. The first substrate (100) may include the polyethylene terephthalate in an amount of about 98 wt% or more based on the total composition.
[0034] The first substrate (100) may comprise a polyethylene terephthalate film that is uniaxially or biaxially stretched. The first substrate (100) may comprise a polyethylene terephthalate film that is stretched about 2 to about 5 times in the length direction and / or width direction.
[0035] The first substrate (100) above may have high mechanical properties to reinforce the glass when applied to a window of a building or vehicle.
[0036] The first substrate (100) may have a tensile strength of about 7 kgf / mm² to about 40 kgf / mm² in the longitudinal direction. The first substrate (100) may have a tensile strength of about 8 kgf / mm² to about 35 kgf / mm² in the longitudinal direction.
[0037] The first substrate (100) may have a tensile strength of about 7 kgf / mm² to about 40 kgf / mm² in the width direction. The first substrate (100) may have a tensile strength of about 8 kgf / mm² to about 35 kgf / mm² in the width direction.
[0038] The first substrate (100) may have a modulus of about 200 kgf / mm² to about 400 kgf / mm² in the longitudinal direction. The first substrate (100) may have a modulus of about 250 kgf / mm² to about 350 kgf / mm² in the longitudinal direction. The first substrate (100) may have a modulus of about 250 kgf / mm² to about 270 kgf / mm² in the longitudinal direction.
[0039] The first substrate (100) may have a modulus of about 200 kgf / mm² to about 400 kgf / mm² in the width direction. The first substrate (100) may have a modulus of about 250 kgf / mm² to about 350 kgf / mm² in the width direction. The first substrate (100) may have a modulus of about 250 kgf / mm² to about 270 kgf / mm² in the width direction.
[0040] The first substrate (100) may have an elongation at break of about 30% to about 150% in the longitudinal direction. The first substrate (100) may have an elongation at break of about 30% to about 130% in the longitudinal direction. The first substrate (100) may have an elongation at break of about 40% to about 120% in the longitudinal direction.
[0041] The first substrate (100) may have an elongation at break of about 30% to about 150% in the longitudinal direction. The first substrate (100) may have an elongation at break of about 30% to about 130% in the longitudinal direction. The first substrate (100) may have an elongation at break of about 40% to about 120% in the longitudinal direction.
[0042] The first substrate (100) may have an elongation at break of about 30% to about 150% in the width direction. The first substrate (100) may have an elongation at break of about 30% to about 130% in the width direction. The first substrate (100) may have an elongation at break of about 40% to about 120% in the width direction.
[0043] The above modulus, the above elongation at break, and the above tensile strength can be measured according to KS B 5521.
[0044] In addition, the modulus, tensile strength, and elongation at break can be measured according to ASTM D882.
[0045] Since the first substrate (100) has such enhanced mechanical strength as described above, it can efficiently protect the first transparent electrode (300), the second transparent electrode (400), the first color-changing layer (500), the second color-changing layer (600), and the electrolyte layer (800). In addition, since the first substrate (100) has such enhanced mechanical strength as described above, it can efficiently reinforce the mechanical strength of the glass to be attached.
[0046] In addition, the first substrate (100) may have high chemical resistance. Accordingly, even if the electrolyte contained in the electrolyte leaks out onto the first substrate (100), damage to the surface of the first substrate (100) can be minimized.
[0047] The first substrate (100) may have enhanced optical properties. The total light transmittance of the first substrate (100) may be about 55% or more. The total light transmittance of the first substrate (100) may be about 70% or more. The total light transmittance of the first substrate (100) may be about 75% to about 99%. The total light transmittance of the first substrate (100) may be about 80% to about 99%.
[0048] The haze of the first substrate (100) may be less than about 20%. It may be about 0.1% to about 20%. The haze of the first substrate (100) may be about 0.1% to about 10%. The haze of the first substrate (100) may be about 0.1% to about 7%.
[0049] The above light transmittance and haze can be measured according to ASTM D 1003, etc.
[0050] Since the first substrate (100) has appropriate light transmittance and haze, the electrochromic element according to the embodiment can have improved optical properties. That is, since the first substrate (100) has appropriate transmittance and haze, the electrochromic element according to the embodiment can be applied to a window to appropriately control transmittance, minimize distortion of the image from the outside, and have an improved appearance.
[0051] Additionally, the first substrate (100) may have an in-plane phase difference of about 100 nm to about 4000 nm. The first substrate (100) may have an in-plane phase difference of about 200 nm to about 3500 nm. The first substrate (100) may have an in-plane phase difference of about 200 nm to about 3000 nm.
[0052] The first substrate (100) may have an in-plane phase difference of about 7,000 nm or more. The first substrate (100) may have an in-plane phase difference of about 7,000 nm to about 50,000 nm. The first substrate (100) may have an in-plane phase difference of about 8,000 nm to about 20,000 nm.
[0053] The above-mentioned in-plane phase difference can be derived from the refractive index and thickness according to the direction of the first substrate (100).
[0054] Since the first substrate (100) has an in-plane phase difference as described above, the electrochromic film according to the embodiment can have an improved appearance.
[0055] The thickness of the first substrate (100) may be about 10 µm to about 200 µm. The thickness of the first substrate (100) may be about 23 µm to about 150 µm. The thickness of the first substrate (100) may be about 30 µm to about 120 µm.
[0056] The first substrate (100) may include an organic or inorganic filler. The organic or inorganic filler may perform the function of an anti-blocking agent.
[0057] The average particle size of the above filler may be about 0.1 µm to about 5 µm. The average particle size of the above filler may be about 0.1 µm to about 3 µm. The average particle size of the above filler may be about 0.1 µm to about 1 µm.
[0058] The above filler may be selected from at least one of the group consisting of silica particles, barium sulfate particles, alumina particles, or titania particles.
[0059] Additionally, the filler may be included in the first substrate (100) in an amount of about 0.01 wt% to about 3 wt% based on the entire first substrate (100). The filler may be included in the first substrate (100) in an amount of about 0.05 wt% to about 2 wt% based on the entire first substrate (100).
[0060] The first substrate (100) may have a single-layer structure. For example, the first substrate (100) may be a single-layer polyester film.
[0061] The first substrate (100) may have a multilayer structure. For example, the first substrate (100) may be a multilayer co-extruded film. The multilayer co-extruded structure may include a core layer, a first surface layer, and a second surface layer. The filler may be included in the first surface layer and the second surface layer.
[0062] The second substrate (200) faces the first substrate (100). The second substrate (200) is placed on the first substrate (100). One end of the second substrate (200) may be positioned so as to be offset from one end of the first substrate (100). The other end of the second substrate (200) may be positioned so as to be offset from the other end of the first substrate (100).
[0063] The second substrate (200) supports the first transparent electrode (300), the first color-changing layer (500), the second color-changing layer (600), the second transparent electrode (400), the lithium-rich layer (700), and the electrolyte layer (800) together with the first substrate (100).
[0064] Additionally, the second substrate (200) sandwiches the first transparent electrode (300), the first color-changing layer (500), the second color-changing layer (600), the second transparent electrode (400), the lithium-rich layer (700), and the electrolyte layer (800) together with the first substrate (100). The second substrate (200) can protect the first transparent electrode (300), the first color-changing layer (500), the second color-changing layer (600), the second transparent electrode (400), the lithium-rich layer (700), and the electrolyte layer (800) from external physical and chemical shocks together with the first substrate (100).
[0065] The second substrate (200) may include a polymer resin. The second substrate (200) may include at least one from the group consisting of a polyester resin, a polyimide resin, a cyclic olefin polymer resin, a polyethersulfone, a polycarbonate, or a polyolefin resin.
[0066] The second substrate (200) may include a polyester resin as a main component. The second substrate (200) may include polyethylene terephthalate. The second substrate (200) may include the polyethylene terephthalate in an amount of about 90 wt% or more based on the total composition. The second substrate (200) may include the polyethylene terephthalate in an amount of about 95 wt% or more based on the total composition. The second substrate (200) may include the polyethylene terephthalate in an amount of about 97 wt% or more based on the total composition. The second substrate (200) may include the polyethylene terephthalate in an amount of about 98 wt% or more based on the total composition.
[0067] The second substrate (200) may comprise a uniaxially or biaxially stretched polyethylene terephthalate film. The second substrate (200) may comprise a polyethylene terephthalate film stretched about 2 to about 5 times in the length direction and / or width direction.
[0068] The second substrate (200) may have high mechanical properties to reinforce the glass when applied to a window of a building or vehicle.
[0069] The second substrate (200) may have a tensile strength of about 7 kgf / mm² to about 40 kgf / mm² in the longitudinal direction. The second substrate (200) may have a tensile strength of about 8 kgf / mm² to about 35 kgf / mm² in the longitudinal direction.
[0070] The second substrate (200) may have a tensile strength of about 7 kgf / mm² to about 40 kgf / mm² in the width direction. The second substrate (200) may have a tensile strength of about 8 kgf / mm² to about 35 kgf / mm² in the width direction.
[0071] The second substrate (200) may have a modulus of about 200 kgf / mm² to about 400 kgf / mm² in the longitudinal direction. The second substrate (200) may have a modulus of about 250 kgf / mm² to about 350 kgf / mm² in the longitudinal direction. The second substrate (200) may have a modulus of about 250 kgf / mm² to about 270 kgf / mm² in the longitudinal direction.
[0072] The second substrate (200) may have a modulus of about 200 kgf / mm² to about 400 kgf / mm² in the width direction. The second substrate (200) may have a modulus of about 250 kgf / mm² to about 350 kgf / mm² in the width direction. The second substrate (200) may have a modulus of about 250 kgf / mm² to about 270 kgf / mm² in the width direction.
[0073] The second substrate (200) may have an elongation at break of about 30% to about 150% in the longitudinal direction. The second substrate (200) may have an elongation at break of about 30% to about 130% in the longitudinal direction. The second substrate (200) may have an elongation at break of about 40% to about 120% in the longitudinal direction.
[0074] The second substrate (200) may have an elongation at break of about 30% to about 150% in the longitudinal direction. The second substrate (200) may have an elongation at break of about 30% to about 130% in the longitudinal direction. The second substrate (200) may have an elongation at break of about 40% to about 120% in the longitudinal direction.
[0075] The second substrate (200) may have a fracture elongation of about 30% to about 150% in the width direction. The second substrate (200) may have a fracture elongation of about 30% to about 130% in the width direction. The second substrate (200) may have a fracture elongation of about 40% to about 120% in the width direction.
[0076] Since the second substrate (200) has such enhanced mechanical strength as described above, it can efficiently protect the first transparent electrode (300), the second transparent electrode (400), the first color-changing layer (500), the second color-changing layer (600), and the electrolyte layer (800). Additionally, since the second substrate (200) has such enhanced mechanical strength as described above, it can efficiently reinforce the mechanical strength of the glass to be attached.
[0077] In addition, the second substrate (200) may have high chemical resistance. Accordingly, even if the electrolyte contained in the electrolyte leaks out onto the second substrate (200), damage to the surface of the second substrate (200) can be minimized.
[0078] The second substrate (200) may have enhanced optical properties. The total light transmittance of the second substrate (200) may be about 55% or more. The total light transmittance of the second substrate (200) may be about 70% or more. The total light transmittance of the second substrate (200) may be about 75% to about 99%. The total light transmittance of the second substrate (200) may be about 80% to about 99%.
[0079] The haze of the second substrate (200) may be less than about 20%. It may be about 0.1% to about 20%. The haze of the second substrate (200) may be about 0.1% to about 10%. The haze of the second substrate (200) may be about 0.1% to about 7%.
[0080] Since the second substrate (200) has appropriate light transmittance and haze, the electrochromic element according to the embodiment can have improved optical properties. That is, since the second substrate (200) has appropriate transmittance and haze, the electrochromic element according to the embodiment can be applied to a window to appropriately control transmittance, minimize distortion of the image from the outside, and have an improved appearance.
[0081] Additionally, the second substrate (200) may have an in-plane phase difference of about 100 nm to about 4000 nm. The second substrate (200) may have an in-plane phase difference of about 200 nm to about 3500 nm. The second substrate (200) may have an in-plane phase difference of about 200 nm to about 3000 nm.
[0082] The second substrate (200) may have an in-plane phase difference of about 7,000 nm or more. The second substrate (200) may have an in-plane phase difference of about 7,000 nm to about 50,000 nm. The second substrate (200) may have an in-plane phase difference of about 8,000 nm to about 20,000 nm.
[0083] The above-mentioned in-plane phase difference can be derived from the refractive index and thickness according to the direction of the second substrate (200).
[0084] Since the second substrate (200) has an in-plane phase difference as described above, the electrochromic element according to the embodiment can have an improved appearance.
[0085] The thickness of the second substrate (200) may be about 10 µm to about 200 µm. The thickness of the first substrate (100) may be about 23 µm to about 150 µm. The thickness of the first substrate (100) may be about 30 µm to about 120 µm.
[0086] The second substrate (200) may include an organic or inorganic filler. The organic or inorganic filler may perform the function of an anti-blocking agent.
[0087] The average particle size of the above filler may be about 0.1 µm to about 5 µm. The average particle size of the above filler may be about 0.1 µm to about 3 µm. The average particle size of the above filler may be about 0.1 µm to about 1 µm.
[0088] The above filler may be selected from at least one of the group consisting of silica particles, barium sulfate particles, alumina particles, or titania particles.
[0089] Additionally, the filler may be included in the second substrate (200) in an amount of about 0.01 wt% to about 3 wt% based on the entire second substrate (200). The filler may be included in the second substrate (200) in an amount of about 0.05 wt% to about 2 wt% based on the entire second substrate (200).
[0090] The second substrate (200) may have a single-layer structure. For example, the second substrate (200) may be a single-layer polyester film.
[0091] The second substrate (200) may have a multilayer structure. For example, the second substrate (200) may be a multilayer co-extruded film.
[0092] The first substrate (100) and the second substrate (200) may be flexible. Accordingly, the electrochromic element according to the embodiment may be flexible overall.
[0093] The first transparent electrode (300) is disposed on the first substrate (100). The first transparent electrode (300) may be formed by deposition on the first substrate (100). Additionally, a hard coating layer may be further included between the first transparent electrode (300) and the first substrate (100).
[0094] The first transparent electrode (300) may include at least one from the group consisting of tin oxide, zinc oxide, silver (Ag), chromium (Cr), indium tin oxide (ITO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), antimony-doped tin oxide (ATO), indium zinc oxide (IZO), niobium-doped titanium oxide (NTO), or cadmium tin oxide (CTO).
[0095] Additionally, the first transparent electrode (300) may include graphene, silver nanowires and / or a metal mesh.
[0096] The first transparent electrode (300) may have an overall light transmittance of about 80% or more. The first transparent electrode (300) may have an overall light transmittance of about 85% or more. The first transparent electrode (300) may have an overall light transmittance of about 88% or more.
[0097] The first transparent electrode (300) may have a haze of less than about 10%. The first transparent electrode (300) may have a haze of less than about 7%. The first transparent electrode (300) may have a haze of less than about 5%.
[0098] The sheet resistance of the first transparent electrode (300) may be approximately 1 Ω / sq to 60 Ω / sq. The sheet resistance of the first transparent electrode (300) may be approximately 1 Ω / sq to 40 Ω / sq. The sheet resistance of the first transparent electrode (300) may be approximately 1 Ω / sq to 30 Ω / sq.
[0099] The thickness of the first transparent electrode (300) may be about 50 nm to about 50 µm. The thickness of the first transparent electrode (300) may be about 100 nm to about 10 µm. The thickness of the first transparent electrode (300) may be about 150 nm to about 5 µm.
[0100] The first transparent electrode (300) is electrically connected to the first color-changing layer (500). Additionally, the first transparent electrode (300) is electrically connected to the electrolyte layer (800) through the first color-changing layer (500).
[0101] The second transparent electrode (400) is disposed below the second substrate (200). The second transparent electrode (400) may be formed by depositing it on the second substrate (200). Additionally, a hard coating layer may be further included between the second transparent electrode (400) and the second substrate (200).
[0102] The second transparent electrode (400) may include at least one from the group consisting of tin oxide, zinc oxide, silver (Ag), chromium (Cr), indium tin oxide (ITO), fluorine-doped tin oxide (FTO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), antimony-doped tin oxide (ATO), indium zinc oxide (IZO), niobium-doped titanium oxide (NTO), or cadmium tin oxide (CTO).
[0103] Additionally, the second transparent electrode (400) may include graphene, silver nanowires and / or a metal mesh.
[0104] The second transparent electrode (400) may have an overall light transmittance of about 80% or more. The second transparent electrode (400) may have an overall light transmittance of about 85% or more. The second transparent electrode (400) may have an overall light transmittance of about 88% or more.
[0105] The second transparent electrode (400) may have a haze of less than about 10%. The second transparent electrode (400) may have a haze of less than about 7%. The second transparent electrode (400) may have a haze of less than about 5%.
[0106] The sheet resistance of the second transparent electrode (400) may be approximately 1 Ω / sq to 60 Ω / sq. The sheet resistance of the second transparent electrode (400) may be approximately 1 Ω / sq to 40 Ω / sq. The sheet resistance of the second transparent electrode (400) may be approximately 1 Ω / sq to 30 Ω / sq.
[0107] The thickness of the second transparent electrode (400) may be about 50 nm to about 50 µm. The thickness of the second transparent electrode (400) may be about 100 nm to about 10 µm. The thickness of the second transparent electrode (400) may be about 150 nm to about 5 µm.
[0108] The second transparent electrode (400) is electrically connected to the second color-changing layer (600). Additionally, the second transparent electrode (400) is electrically connected to the electrolyte layer (800) through the second color-changing layer (600).
[0109] The first color-changing layer (500) is placed on the first transparent electrode (300). The first color-changing layer (500) may be placed directly on the upper surface of the first transparent electrode (300). The first color-changing layer (500) may be electrically directly connected to the first transparent electrode (300).
[0110] The first color-changing layer (500) is electrically connected to the first transparent electrode (300). The first color-changing layer (500) may be directly connected to the first transparent electrode (300). Additionally, the first color-changing layer (500) is electrically connected to the electrolyte layer (800). The first color-changing layer (500) may be electrically connected to the electrolyte layer (800).
[0111] The first color-changing layer (500) may change color by receiving electrons. The first color-changing layer (500) may include a first electrochromic material that changes color by receiving electrons. The first electrochromic material may include at least one from the group consisting of tungsten oxide, niobium pentaoxide, vanadium pentaoxide, titanium oxide, molybdenum oxide, vilogen, or poly(3,4-ethylenedioxythiophene; PEDOT).
[0112] The first color-changing layer (500) may include the first electrochromic material in the form of particles. The tungsten oxide, niobium pentaoxide, vanadium pentaoxide, titanium oxide, and molybdenum oxide may be particles having an average particle size of about 1 nm to about 200 nm. The average particle size of the first electrochromic material may be about 5 nm to about 100 nm. The average particle size of the first electrochromic material may be about 10 nm to about 50 nm.
[0113] The first color-changing layer (500) may contain the first electrochromic material in an amount of about 70 wt% to about 98 wt% based on the total weight of the first color-changing layer (500). The first color-changing layer (500) may contain the first electrochromic material in an amount of about 80 wt% to about 96 wt% based on the total weight of the first color-changing layer (500). The first color-changing layer (500) may contain the first electrochromic material in an amount of about 85 wt% to about 94 wt% based on the total weight of the first color-changing layer (500).
[0114] Since the first color-changing layer (500) contains the first electrochromic material in the average particle size and weight range, the electrochromic element according to the embodiment can have improved optical properties and electrochromic properties.
[0115] Additionally, the first discoloration layer (500) may further include a binder. The binder may be an inorganic binder. The binder may include silica gel. The binder may be formed by a silica sol containing tetramethoxysilane or methyltrimethoxysilane.
[0116] The first color-changing layer (500) may contain the binder in an amount of about 1 wt% to 20 wt% based on the total weight of the first color-changing layer (500). The first color-changing layer (500) may contain the binder in an amount of about 5 wt% to 15 wt% based on the total weight of the first color-changing layer (500). The first color-changing layer (500) may contain the binder in an amount of about 7 wt% to 13 wt% based on the total weight of the first color-changing layer (500).
[0117] The second color-changing layer (600) is placed below the second transparent electrode (400). The second color-changing layer (600) may be placed directly on the lower surface of the second transparent electrode (400). The second color-changing layer (600) may be electrically directly connected to the second transparent electrode (400).
[0118] The second color-changing layer (600) is electrically connected to the second transparent electrode (400). The second color-changing layer (600) may be directly connected to the second transparent electrode (400). Additionally, the second color-changing layer (600) is electrically connected to the electrolyte layer (800). The second color-changing layer (600) may be electrically connected to the electrolyte layer (800).
[0119] The second color-changing layer (600) may change color as it loses electrons. The second color-changing layer (600) may include a second electrochromic material that changes color by oxidizing as it loses electrons. The second color-changing layer (600) may include at least one from the group consisting of Prussian blue, nickel oxide, and iridium oxide.
[0120] The second color-changing layer (600) may include the second electrochromic material in the form of particles. The Prussian blue, nickel oxide, and iridium oxide may be particles having a particle size of about 1 nm to about 200 nm.
[0121] Additionally, the second discoloration layer (600) may further include the binder.
[0122] Additionally, the second color-changing layer (600) may contain lithium. The lithium may diffuse from the lithium-rich layer (700) into the second color-changing layer (600) and be injected into the second color-changing layer (600) in the form of ions. That is, the second color-changing layer (600) may contain lithium ions. The lithium may be combined with the second electrochromic material and included in the second color-changing layer (600).
[0123] In the second discoloration layer (600) above, the concentration of lithium ions may be about 0.1 wt% to about 10 wt%, about 0.5 wt% to about 15 wt%, about 0.1 wt% to about 5 wt%, about 0.1 wt% to about 3 wt%, or about 1 wt% to about 10 wt%.
[0124] Since the above-mentioned discoloration layer contains the lithium in the above-mentioned amount, it can have an improved discoloration speed and improved durability.
[0125] Additionally, in the second color-changing layer (600), the concentration of lithium ions can become progressively smaller as it goes from the lithium-rich layer (700) to the second transparent electrode. That is, in the second color-changing layer (600), the concentration of lithium can become progressively smaller as it goes upward.
[0126] In the second discoloration layer (600) above, the difference between the concentration of lithium at the top and the concentration of lithium at the bottom may be about 0.1 wt% to about 5 wt%, about 0.3 wt% to about 3 wt%, about 0.5 wt% to about 5 wt%, about 1 wt% to about 10 wt%, or about 0.7 wt% to about 7 wt%.
[0127] At the top of the second discoloration layer (600), the concentration of lithium may be about 0 wt% to about 3 wt%, about 0 wt% to about 2 wt%, about 0 wt% to about 1.5 wt%, or about 0 wt% to about 1 wt%.
[0128] At the bottom of the second discoloration layer (600), the concentration of lithium may be about 3 wt% to about 10 wt%, about 4 wt% to about 15 wt%, about 3 wt% to about 15 wt%, or about 5 wt% to about 10 wt%.
[0129] In the second discoloration layer (600) above, the concentration of lithium may be the concentration in the initial state.
[0130] Additionally, as previously explained, the second color-changing layer (600) may include particles containing the second electrochromic material. That is, the second color-changing layer (600) may include electrochromic particles. The electrochromic particles may include the second electrochromic material.
[0131] In the above electrochromic particles, the concentration of lithium can gradually decrease from the outermost layer to the center.
[0132] In the electrochromic particles above, the difference between the concentration of lithium at the center and the concentration of lithium at the outermost layer may be about 0.1 wt% to about 5 wt%, about 0.3 wt% to about 3 wt%, about 0.5 wt% to about 5 wt%, about 1 wt% to about 10 wt%, or about 0.7 wt% to about 7 wt%.
[0133] At the center of the electrochromic particles, the concentration of lithium may be about 0 wt% to about 3 wt%, about 0 wt% to about 2 wt%, about 0 wt% to about 1.5 wt%, or about 0 wt% to about 1 wt%.
[0134] At the outermost part of the electrochromic particles, the concentration of lithium may be about 3 wt% to about 10 wt%, about 4 wt% to about 15 wt%, about 3 wt% to about 15 wt%, or about 5 wt% to about 10 wt%.
[0135] Since the second discoloration layer (600) contains the lithium in the same content as above, it can have improved discoloration speed and durability.
[0136] The lithium-rich layer (700) is placed below the second color-changing layer (600). The lithium-rich layer (700) may be adjacent to the lower surface of the second color-changing layer (600). The lithium-rich layer (700) may be in direct contact with the lower surface of the second color-changing layer (600).
[0137] Additionally, the lithium-rich layer (700) is disposed on the electrolyte layer (800). The lithium-rich layer (700) may be adjacent to the upper surface of the electrolyte layer (800). The lithium-rich layer (700) may be in direct contact with the upper surface of the electrolyte layer (800).
[0138] That is, the lithium-rich layer (700) is disposed between the second color-changing layer (600) and the electrolyte layer (800). The lithium-rich layer (700) can be sandwiched between the second color-changing layer (600) and the electrolyte layer (800).
[0139] The lithium-rich layer (700) may include lithium hydroxide. The lithium-rich layer (700) may include lithium at a high concentration. The lithium-rich layer (700) may be formed by combining lithium with the electrochromic particles included in the second electrochromic layer (600). That is, the lithium-rich layer (700) may be formed by combining the second electrochromic material and the lithium ions. That is, the lithium-rich layer (700) may include a compound of the second electrochromic material and the lithium.
[0140] The lithium-rich layer (700) may contain the lithium at a higher concentration than the second discoloration layer (600). Additionally, the lithium-rich layer (700) may contain the lithium at a higher concentration than the electrolyte layer (800).
[0141] In the lithium-rich layer (700), the concentration of lithium may be about 5 wt% to about 30 wt%, about 7 wt% to about 30 wt%, about 3 wt% to about 20 wt%, about 10 wt% to about 30 wt%, about 5 wt% to about 20 wt%, or about 3 wt% to about 15 wt%.
[0142] The concentration of lithium in the lithium-rich layer (700) may be greater than the concentration of lithium in the second discoloration layer (600) by about 0.1 wt% to about 5 wt%, about 1 wt% to about 10 wt%, about 3 wt% to about 10 wt%, about 0.5 wt% to about 5 wt%, about 5 wt% to about 15 wt%, or about 0.1 wt% to about 10 wt%.
[0143] The thickness of the lithium-rich layer (700) may be about 10 nm to about 1000 nm, about 1 nm to about 500 nm, about 1 nm to about 300 nm, about 1 nm to about 200 nm, about 100 nm to about 1000 nm, about 50 nm to about 500 nm, about 0.5 nm to about 500 nm, about 0.3 nm to about 30 nm, about 0.1 nm to about 10 nm, or about 1 nm to about 100 nm.
[0144] Since the lithium-rich layer (700) has the above-described characteristics, the electrochromic device according to the embodiment can have improved discoloration speed and durability. In particular, the lithium-rich layer (700) can rapidly supply lithium to the second discoloration layer (600) during the discoloration process. Accordingly, the electrochromic device according to the embodiment can have improved discoloration speed and durability.
[0145] The second substrate (200), the second transparent electrode (400), the second color-changing layer (600), and the lithium-rich layer (700) are included in the second laminate. That is, the second laminate includes the second substrate (200), the second transparent electrode (400), the second color-changing layer (600), and the lithium-rich layer (700). The second laminate may be composed of the second substrate (200), the second transparent electrode (400), the second color-changing layer (600), and the lithium-rich layer (700).
[0146] The electrolyte layer (800) is placed on the first color-changing layer (500). Additionally, the electrolyte layer (800) is placed below the second color-changing layer (600). The electrolyte layer (800) is placed below the lithium-rich layer (700). The electrolyte layer (800) is placed between the first color-changing layer (500) and the lithium-rich layer (700).
[0147] The above electrolyte layer (800) may include a solid polymer electrolyte containing metal ions or an inorganic hydrate, etc. The above electrolyte layer (800) may include lithium ions (Li+), sodium ions (Na+), potassium ions (K+), etc.
[0148] Specifically, Poly-AMPS, PEO / LiCF3SO3, etc. can be used as the solid polymer electrolyte, and Sb2O5·4H2O, etc. can be used as the inorganic hydrate.
[0149] Additionally, the electrolyte layer (800) is configured to provide electrolyte ions involved in the electrochromic reaction. The electrolyte ions may be monovalent cations, such as, for example, H+, Li+, Na+, K+, Rb+, or Cs+.
[0150] The above electrolyte layer (800) may include an electrolyte. Examples of the electrolyte may include liquid electrolytes, gel polymer electrolytes, or inorganic solid electrolytes without limitation. Additionally, the electrolyte may be used in the form of a single layer or film so as to be laminated together with the electrode or substrate.
[0151] The type of electrolyte salt used in the electrolyte layer (800) is not particularly limited as long as it includes a compound capable of providing a monovalent cation, namely H+, Li+, Na+, K+, Rb+, or Cs+. For example, the electrolyte layer (800) may be LiClO4, LiBF4, LiAsF6, LiPF6, LiCl, LiBr, LiI, or LiB 10 Cl 10 It may include lithium salt compounds such as LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li or (CF3SO2)2NLi; or sodium salt compounds such as NaClO4.
[0152] In one example, the electrolyte layer (800) may include a compound containing Cl or F as an electrolyte salt. Specifically, the electrolyte layer (800) may include LiClO4, LiBF4, LiAsF6, LiPF6, LiCl, and LiB 10 Cl 10 It may include one or more electrolyte salts selected from LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CF3SO3Li, (CF3SO2)2NLi, and NaClO4.
[0153] The above electrolyte may additionally include a carbonate compound as a solvent. Since carbonate compounds have a high dielectric constant, they can increase ionic conductivity. As a non-limiting example, solvents such as PC (propylene carbonate), EC (ethylene carbonate), DMC (dimethyl carbonate), DEC (diethyl carbonate), or EMC (ethylmethyl carbonate) may be used as carbonate compounds.
[0154] In another example, where the electrolyte layer (800) comprises a gel polymer electrolyte, the electrolyte layer (800) comprises poly-vinyl sulfonic acid, poly-styrene sulfonic acid, polyethylene sulfonic acid, poly-2-acrylamido-2-methyl-propane sulfonic acid, poly-perfluoro sulfonic acid, poly-toluene sulfonic acid, poly-vinyl alcohol, poly-ethylene imine, poly-vinyl pyrrolidone, poly-ethylene oxide (PEO), poly-propylene oxide (PPO), poly-(ethylene Poly-(ethylene oxide, siloxane) (PEOS), Poly-(ethylene glycol, siloxane) (poly-(ethylene glycol, siloxane)), Poly-(propylene oxide, siloxane) (poly-(propylene oxide, siloxane)), Poly-(ethylene oxide, methyl methacrylate) (poly-(ethylene oxide, methyl methacrylate) (PEO-PMMA)), Poly-(ethylene oxide, acrylic acid) (poly-(ethylene oxide, acrylic acid) (PEO-PAA)), Poly-(propylene glycol, methyl methacrylate) (poly-(propylene glycol, methyl methacrylate) (PPG-PMMA)),It may include polymers such as poly-ethylene succinate or poly-ethylene adipate. In one example, a mixture of two or more of the polymers listed above or two or more copolymers may be used as a polymer electrolyte.
[0155] Additionally, the electrolyte layer (800) may include a curable resin that can be cured by ultraviolet irradiation or heat. The curable resin may be selected from at least one of the group consisting of acrylate-based oligomers, polyethylene glycol-based oligomers, urethane-based oligomers, polyester-based oligomers, polyethylene glycol dimethyl, or polyethylene glycol diacrylate. Additionally, the electrolyte layer (800) may include a photocuring initiator and / or a thermal curing initiator.
[0156] The thickness of the electrolyte layer (800) may be about 10 μm to about 200 μm. The thickness of the electrolyte layer (800) may be about 50 μm to about 150 μm.
[0157] The electrolyte layer (800) may have a transmittance within the range of 60% to 95%. Specifically, the electrolyte layer (800) may have a transmittance of 60% to 95% for visible light in the wavelength range of 380 nm to 780 nm, more specifically, 400 nm or 550 nm. The transmittance may be measured using a known haze meter (HM).
[0158] The electrochromic element according to the embodiment may further include a sealing portion (not shown).
[0159] The sealing portion comprises a curable resin. The sealing portion may comprise a thermosetting resin and / or a photosetting resin.
[0160] Examples of the above-mentioned thermosetting resins include epoxy resin, melamine resin, urea resin, or unsaturated polyester resin. In addition, examples of the above-mentioned epoxy resins include phenol novolak type epoxy resin, cresol novolak type epoxy resin, biphenyl novolak type epoxy resin, trisphenol novolak type epoxy resin, dicyclopentadiene novolak type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, 2,2'-dialyrbisphenor A type epoxy resin, bisphenol S type epoxy resin, hydrogenated bisphenol A type epoxy resin, propylene oxide added bisphenol A type epoxy resin, biphenyl type epoxy resin, naphthalene type epoxy resin, resorcinol type epoxy resin, or glycidyl amines.
[0161] In addition, the seal may further include a heat-curing agent. Hydrazide compounds such as 1,3-bis[hydrazinocarbonoethyl 5-isopropylhydantoin], adipic acid dihydrazide, etc.; dicyandiamide, guanidine derivatives, 1-cyanoethyl-2-phenylimidazole, N-[2-(2-methyl-1-imidazolyl)ethyl]urea, 2,4-diamino-6-[2'-methylimidazolyl(1')]-ethyl-s-thoriazine, N,N'-bis(2-methyl-1-imidazolyl ethyl)urea, N,N'-(2-methyl-1-imidazolyl ethyl)-azipoamido, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2-imidazolin-2-thiol, 2,2'-thiozy Examples include ethanethiol, various amines, and addition products of epoxy resins.
[0162] The first sealing portion may include a photocurable resin. Examples of the photocurable resin include acrylate-based resins such as urethane acrylate. Additionally, the sealing portion may further include a photocuring initiator. The photocuring initiator may be selected from at least one group consisting of acetophenone-based compounds, benzophenone-based compounds, thioxantone-based compounds, benzoin-based compounds, triazine-based compounds, or oxime-based compounds.
[0163] Additionally, the seal may further include a hygroscopic agent such as zeolite and / or silica. Additionally, the seal may further include an inorganic filler. The inorganic filler may be a material with high insulation, transparency, and durability. Examples of the inorganic filler include silicon, aluminum, zirconia, or mixtures thereof.
[0164] In addition, the electrochromic element according to the embodiment may further include a first bus bar (not shown) and a second bus bar (not shown).
[0165] The first bus bar may be placed on the first transparent electrode (300). The first bus bar may be connected to the first transparent electrode (300).
[0166] The first bus bar may be electrically connected to the first transparent electrode (300). The first bus bar may be in direct contact with the upper surface of the first transparent electrode (300). The first bus bar may be connected to the first transparent electrode (300) through solder.
[0167] The second bus bar is positioned below the second transparent electrode (400). The second bus bar is connected to the second transparent electrode (400).
[0168] The second bus bar may be electrically connected to the second transparent electrode (400). The second bus bar may be in direct contact with the lower surface of the second transparent electrode (400). The second bus bar may be connected to the second transparent electrode (400) through solder.
[0169] The first bus bar and / or the second bus bar may comprise a metal. The first bus bar and / or the second bus bar may comprise a metal ribbon. The first bus bar and / or the second bus bar may comprise a conductive paste. The first bus bar and / or the second bus bar may comprise a binder and a conductive filler.
[0170] An electrochromic element according to an embodiment can be manufactured by the following method. FIGS. 2 to 5 are cross-sectional views illustrating the process of manufacturing an electrochromic element according to an embodiment.
[0171] Referring to FIG. 2, a first transparent electrode (300) is formed on a first substrate (100). The first transparent electrode (300) can be formed by a vacuum deposition process. A metal oxide, such as indium tin oxide, can be deposited on the first substrate (100) by a sputtering process or the like to form the first transparent electrode (300).
[0172] The first transparent electrode (300) can be formed by a coating process. The first transparent electrode (300) can be formed by coating a nano metal wire together with a binder on the first substrate (100). The first transparent electrode (300) can be formed by coating a conductive polymer on the first substrate (100).
[0173] Additionally, the first transparent electrode (300) can be formed by a patterning process. A metal layer is formed on the first substrate (100) by a sputtering process or the like, and the metal layer is patterned so that a first transparent electrode (300) layer including a metal mesh can be formed on the first substrate (100).
[0174] Subsequently, a first color-changing layer (500) is formed on the first transparent electrode (300) layer. The first color-changing layer (500) can be formed by a sol-gel coating process. A first sol solution containing a first electrochromic material, a binder, and a solvent can be coated on the first transparent electrode (300) layer. A sol-gel reaction occurs in the coated first sol solution, and the first color-changing layer (500) can be formed.
[0175] The first sol solution may contain the first electrochromic material in particle form in an amount of about 5 wt% to about 30 wt% based on the total weight of the solution. The first sol solution may contain the binder in an amount of about 0.5 wt% to about 5 wt% based on the total weight of the solution. The first sol solution may contain the solvent in an amount of about 70 wt% to about 95 wt% based on the total weight of the solution.
[0176] The above first sol solution may additionally include a dispersant.
[0177] The solvent may be selected from at least one group consisting of alcohols, ethers, ketones, esters, or aromatic hydrocarbons. The solvent may be selected from at least one group consisting of ethanol, propanol, butanol, hexanol, cyclohexanol, diacetone alcohol, ethylene glycol, diethylene glycol, glycerin, diethyl ether, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol modobutyl ether, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, propylene glycol monomethyl ether, acetone, methyl ethyl ketone, acetylacetone, methyl isobutyl ketone, cyclohexanone, acetoacetic acid ester, methyl acetate, ethyl acetate, n-propyl acetate, and i-butyl acetate.
[0178] As previously explained, the above binder may be an inorganic binder.
[0179] Afterwards, an electrolyte composition is formed to form an electrolyte layer (800).
[0180] The above electrolyte composition may include a metal salt, an electrolyte, a photocurable resin, and a photocurable initiator. The above photocurable resin may be selected from at least one of the group consisting of hexanediol diacrylate (HDDA), tripropyleneglycoldiacrylate (TPGDA), ethyleneglycoldiacrylate (EGDA), trimethylolpropane triacrylate (TMPTA), trimethylolpropane ethoxylated triacrylate (TMPEOTA), glycerol propoxylated triacrylate (GPTA), pentaerythritol tetraacrylate (PETA), or dipentaerythritol hexaacrylate (DPHA).
[0181] The metal salt, the electrolyte, and the photocuring initiator may be as described above.
[0182] Referring to FIG. 3, the electrolyte composition is coated on the first color-changing layer (500). Accordingly, an electrolyte composition coating layer (801) is formed on the first color-changing layer (500).
[0183] Referring to FIG. 4, a second transparent electrode (400) is formed on a second substrate (200).
[0184] The second transparent electrode (400) can be formed by a vacuum deposition process. A metal oxide, such as indium tin oxide, can be deposited on the second substrate (200) by a sputtering process or the like to form the second transparent electrode (400).
[0185] The second transparent electrode (400) can be formed by a coating process. The second transparent electrode (400) can be formed by coating a nano metal wire together with a binder on the second substrate (200). The second transparent electrode (400) can be formed by coating a conductive polymer on the second substrate (200).
[0186] Additionally, the second transparent electrode (400) can be formed by a patterning process. A metal layer is formed on the second substrate (200) by a sputtering process or the like, and the metal layer is patterned so that a second transparent electrode (400) layer including a metal mesh can be formed on the second substrate (200).
[0187] Subsequently, a second color-changing layer (600) is formed on the second transparent electrode (400) layer. The second color-changing layer (600) can be formed by a sol-gel coating process. A second sol solution containing a second electrochromic material, a binder, and a solvent can be coated on the second transparent electrode (400) layer. A sol-gel reaction occurs in the coated second sol solution, and the second color-changing layer (600) can be formed.
[0188] The second sol solution may contain the second discoloration substance in particle form at a content of about 5 wt% to about 30 wt% based on the total weight of the solution. The second sol solution may contain the binder at a content of about 0.5 wt% to about 5 wt% based on the total weight of the solution. The second sol solution may contain the solvent at a content of about 70 wt% to about 95 wt% based on the total weight of the solution.
[0189] The above second sol solution may additionally include a dispersant.
[0190] Afterwards, the lithium-rich layer (700) is formed on the second discoloration layer (600).
[0191] In order for the lithium-rich layer (700) to be formed, an aqueous lithium hydroxide solution is prepared. The aqueous lithium hydroxide solution comprises deionized water and lithium hydroxide. The lithium hydroxide can be uniformly dissolved in the deionized water.
[0192] In the above lithium hydroxide aqueous solution, the concentration of the lithium hydroxide may be about 0.01 wt% to about 5 wt%.
[0193] Afterwards, the above lithium hydroxide aqueous solution is coated entirely on the second discoloration layer (600).
[0194] Afterwards, the deionized water contained in the coated lithium hydroxide aqueous solution is dried, and the lithium-rich layer (700) can be formed on the second discoloration layer (600).
[0195] In addition, the second laminate having the lithium-rich layer (700) formed thereon can be heat-treated at a temperature of about 60°C to about 150°C for about 5 minutes to about 60 minutes.
[0196] Referring to FIG. 5, the second substrate (200), the second transparent electrode (400), the second color-changing layer (600), and the lithium-rich layer (700) are laminated on the coated electrolyte composition layer (801). That is, the second laminate can be laminated on the coated electrolyte composition layer. At this time, the lithium-rich layer (700) is in direct contact with the coated electrolyte composition layer (801).
[0197] Subsequently, the coated electrolyte composition layer (801) is cured by light, and a first laminate comprising the first substrate (100), the first transparent electrode (300), and the first color-changing layer (500), and a second laminate comprising the second substrate (200), the second transparent electrode (400), and the second color-changing layer (600) are laminated together. That is, the first laminate and the second laminate can be bonded together by the electrolyte layer (800).
[0198] Accordingly, an electrochromic element according to the embodiment can be manufactured.
[0199] In addition, the electrochromic element according to the embodiment may have light transmittance. Here, the light transmittance may refer to the light transmittance based on the state in which the electrochromic element is not electrochromic. In addition, the light transmittance may refer to total light transmittance.
[0200] The light transmittance of the electrochromic element may be about 50% to about 90%. The light transmittance of the electrochromic element may be about 55% to about 88%. The light transmittance of the electrochromic element may be about 68% to about 86%.
[0201] The electrochromic element according to the embodiment has a lithium-rich layer (700). Accordingly, the electrochromic element according to the embodiment can improve the movement speed of lithium ions during the driving process. That is, the lithium-rich layer (700) can supply lithium ions to the second color-changing layer (600) at a high speed, thereby changing the color of the second color-changing layer (600).
[0202] In addition, the second color-changing layer (600) may have an increasingly higher lithium concentration as it gets closer to the lithium-rich layer (700). Accordingly, the electrochromic element according to the embodiment can improve the color change speed in the early stages of color change.
[0203] In addition, since the second color-changing layer (600) is adjacent to the lithium-rich layer (700), it can contain lithium ions at a high concentration. That is, the second color-changing layer (600) can accommodate lithium ions at a high concentration.
[0204] Accordingly, the second color-changing layer (600) can be discolored to have an appropriate color and appropriate transmittance.
[0205] Accordingly, the electrochromic element according to the embodiment can have improved color change speed and color change performance.
[0206] In addition, since the lithium contained in the lithium-rich layer (700) gradually diffuses into the second color-changing layer (600), the electrochromic element according to the embodiment can easily color and decolorize the second color-changing layer (600).
[0207] Accordingly, the electrochromic element according to the embodiment can reduce the chemical shock applied to the second color-changing layer (600) during the coloring and / or decolorization process.
[0208] Accordingly, the electrochromic element according to the embodiment can reduce operating time, reduce discoloration shock, and have improved durability.
[0209] FIG. 6 is a drawing illustrating a window device (1) according to an embodiment.
[0210] Referring to FIG. 6, the window device (1) according to the embodiment includes the electrochromic element (10), a frame (20), windows (31, 32, 33), a plug-in component (40), and a power supply unit (50).
[0211] The frame (20) may be composed of one or more pieces. For example, the frame (20) may be composed of one or more materials such as vinyl, PVC, aluminum (Al), steel, or fiberglass. The frame (20) secures the windows (31, 32, 33) and seals the space between the windows (31, 32, 33). Also,
[0212] The frame (20) may hold or include foam or other material pieces. The frame (20) may include a spacer, and the spacer may be placed between adjacent windows (31, 32, 33). Additionally, the spacer may hermetically seal the space between the windows (31, 32, 33) together with an adhesive sealant.
[0213] The windows (31, 32, 33) are fixed to the frame (20). The windows (31, 32, 33) may be glass panes. The windows (31, 32, 33) may be conventional silicon oxide (SOx)-based glass substrates, such as soda-lime glass or float glass, composed of approximately 75% silica (SiO2) plus Na2O, CaO, and some minor additives. However, any material having suitable optical, electrical, thermal, and mechanical properties may be used. The windows (31, 32, 33) may also include, for example, other glass materials, plastics and thermoplastic resins (e.g., poly(methyl methacrylate), polystyrene, polycarbonate, allyl diglycol carbonate, SAN (styrene acrylonitrile copolymer), poly(4-methyl-1-pentene), polyester, polyamide), or mirror materials. The windows (31, 32, 33) may include tempered glass.
[0214] The above windows (31, 32, 33) may include a first window (31), a second window (32), and a third window (33). The first window (31) and the third window (33) may be positioned at the outermost level, and the second window (32) may be positioned between the first window (31) and the third window (33).
[0215] The electrochromic element (10) is disposed between the first window (31) and the second window (32). The electrochromic element (10) may be laminated to the first window (31) and the second window (32).
[0216] The electrochromic element (10) can be laminated to the first window (31) by a first polyvinyl butyral sheet. That is, the first polyvinyl butyral sheet can be placed on the first window (31) and the electrochromic element (10), and laminated to the first window (31) and the electrochromic element (10).
[0217] The electrochromic element (10) can be laminated to the second window (32) by a second polyvinyl butyral sheet. That is, the second polyvinyl butyral sheet can be placed on the second window (32) and the electrochromic element (10), and laminated to the second window (32) and the electrochromic element (10).
[0218] A spaced-apart space (60) may be formed between the second window (32) and the third window (33). One or more gases, such as argon (Ar), krypton (Kr), or xenon (Xn), may be filled into the space.
[0219] The above windows (31, 32, 33) may be glass paint sizes for residential or commercial window applications. The size of the glass paint may vary widely depending on the specific needs of the residential or commercial company. In some embodiments, the above windows (31, 32, 33) may be formed of architectural glass. Architectural glass is typically used in commercial buildings, but can also be used in residential buildings and typically, although not essential, separates the indoor environment from the outdoor environment. In some embodiments, a suitable architectural glass substrate may be at least approximately 20 inches by approximately 20 inches and may be much larger, for example, approximately 80 inches by approximately 120 inches, or larger. Architectural glass is typically at least about 2 millimeters (mm) thick and may be 6 mm or thicker.
[0220] In one embodiment, the windows (31, 32, 33) may have a thickness in the range of approximately 1 mm to approximately 10 mm.
[0221] In one embodiment, the windows (31, 32, 33) may be very thin and flexible, such as Gorilla Glass® or Willow™ Glass, each of which is commercially available from Corning, Inc. of New York, Corning, and these glasses may have a thickness of less than 0.3 mm or about 1 mm.
[0222] The plug-in component (40) may include a first electric input (41), a second electric input (42), a third electric input (43), a fourth electric input (44), and a fifth electric input (45).
[0223] In addition, the power supply unit (50) includes a first power terminal (51) and a second power terminal (52).
[0224] The first electrical input (41) is electrically coupled to the first power terminal (51) through one or more wires or other electrical connections, components, or devices.
[0225] The first electrical input (41) may include a pin, a socket, or other electrical connector or conductor. Additionally, the first electrical input (41) may be electrically connected to the electrochromic element (10) through a first bus bar (not shown). The first bus bar may be electrically connected to the second transparent electrode (400).
[0226] The second electrical input (42) is electrically coupled to the second power terminal (52) through one or more wires or other electrical connections, components, or devices.
[0227] The second electrical input (42) may include a pin, a socket, or other electrical connector or conductor. Additionally, the second electrical input (42) may be electrically connected to the electrochromic element (10) through a second bus bar (not shown). The second bus bar may be electrically connected to the first transparent electrode (300).
[0228] The above third electrical input (43) can be coupled to a device, system, or building ground.
[0229] The above fourth electrical input (44) and fifth electrical input (45) can be used individually, for example, for communication between a controller or microcontroller controlling the window device (1) and a network controller.
[0230] The power supply unit (50) supplies power to the electrochromic element (10) through the plug-in component (40). Additionally, the power supply unit (50) is controlled by an external controller to supply power of a certain waveform to the electrochromic element (10).
[0231] Furthermore, the features, structures, effects, etc. described in the embodiments above are included in at least one embodiment of the present invention and are not necessarily limited to only one embodiment. Moreover, the features, structures, effects, etc. exemplified in each embodiment may be combined or modified and implemented in other embodiments by a person skilled in the art to which the embodiments belong. Therefore, details regarding such combinations and modifications should be interpreted as being included within the scope of the present invention.
[0232] Although the invention has been described above with reference to embodiments, this is merely illustrative and does not limit the invention. Those skilled in the art will understand that various modifications and applications not exemplified above are possible within the scope of the essential characteristics of the embodiments. For example, each component specifically shown in the embodiments may be modified and implemented. Furthermore, differences related to such modifications and applications should be interpreted as being included within the scope of the invention as defined in the appended claims.
[0234] Preparation Example
[0235] ITO Film: Hansung Industrial Co., Ltd., HI150-ABE-125A-AB
[0236] Tungsten oxide powder dispersion: Adcro Co., Ltd., ELACO-W
[0237] Nickel oxide powder dispersion: Adcro Co., Ltd., ELACO-N
[0238] Lithium hydroxide aqueous solution: Formed by dissolving lithium hydroxide (Duksan General Chemical) in deionized water at a content of approximately 0.1 wt%.
[0239] Gel polymer electrolyte composition
[0240] A gel polymer electrolyte composition was prepared by mixing about 39 parts by weight of dipentaerythritol hexaacrylate (DPHA), about 5 parts by weight of ionic liquid 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide [BMI-TFSI], and about 1 part by weight of diethoxyacetophenone (DEAP), and adding LiBF4 (Li+ concentration: 1 mol / L).
[0242] Example 1
[0243] About 10 parts by weight of tungsten oxide powder, about 1 part by weight of TEOS, and about 90 parts by weight of ethanol were uniformly mixed to prepare a first color-changing material composition. The first color-changing material composition was coated on a first ITO film to a thickness of about 25 μm, and a first color-changing layer having a thickness of about 600 nm was formed by a sol-gel reaction at a temperature of about 110°C for about 5 minutes.
[0244] Approximately 11 parts by weight of nickel oxide powder, approximately 1 part by weight of TEOS, and approximately 89 parts by weight of ethanol were uniformly mixed to prepare a second color-changing material composition. The second color-changing material composition was coated onto a second ITO film to a thickness of approximately 40 μm, and a second color-changing layer having a thickness of 1200 nm was formed by a sol-gel reaction at a temperature of approximately 120°C for approximately 5 minutes. Subsequently, an aqueous lithium hydroxide solution was coated onto the second color-changing layer to a thickness of approximately 4 μm, and drying was carried out at a temperature of approximately 120°C for approximately 5 minutes, thereby forming a lithium-rich layer having a thickness of approximately 0.005 μm. Accordingly, a second laminate comprising the second ITO film, the second color-changing layer, and the lithium-rich layer was prepared. The gel polymer electrolyte composition is coated on the first color-changing layer to a thickness of about 100 μm, and a second ITO film having the second color-changing layer formed thereon is laminated onto the coated gel polymer electrolyte composition, and the coated gel polymer electrolyte composition is cured by UV light. Afterward, the laminate is left at room temperature for about 14 hours to be aged. Accordingly, an electrochromic device according to the example is manufactured.
[0245] Examples 2 to 4 and Comparative Examples
[0246] As shown in Table 1 below, the concentration of the lithium hydroxide aqueous solution was controlled, and the lithium-rich layer was formed.
[0247] division Lithium hydroxide aqueous solution concentration (wt%) Lithium-rich layer thickness (㎛) Example 1 0.1 0.005 Example 2 0.2 0.01 Example 3 0.3 0.015 Example 4 0.4 0.02 Example 5 0.5 0.025 Comparative example - 0
[0249] Evaluation example
[0250] 1. Coloring speed
[0251] In the electrochromic elements (5 cm × 5 cm) prepared in the examples and comparative examples, after being colored by a driving voltage of 1.5 V, they were decolored for a sufficient amount of time. Subsequently, the time until the electrochromic elements prepared in the examples and comparative examples were colored again by the driving voltage and had an total light transmittance of about 15% was measured. The total light transmittance was measured by a solar spectrum meter (EDTM, SS2450) in the wavelength range of about 380 nm to about 780 nm.
[0252] 2. Charge / Discharge Test
[0253] In the electrochromic devices manufactured in the examples and comparative examples, the device is placed inside a solar simulator and exposed to simulated sunlight. Then, the (-) electrode of a charge / discharge tester (Won-A Tech, WBCS_D70714K1) is connected to a busbar attached to tungsten oxide, and the (+) electrode is connected to a busbar attached to nickel oxide. Subsequently, when a predetermined voltage is applied and a sufficiently high decolorization transmittance is reached, the voltages are reversed by internal electrical deformation of the charge / discharge tester so that the (+) voltage is applied to the busbar connected to tungsten oxide and the (-) voltage is applied to the busbar connected to nickel oxide. A charge / discharge test is conducted by measuring the transmittance and charge / discharge amount while continuously repeating cycles, with the point at which a sufficiently low color transmittance is reached being considered one cycle. The number of times the color change range does not decrease after a certain number of cycles and the charge / discharge amount is maintained at 80% or more is measured.
[0254] As shown in Table 2 below, the coloring rate and the number of charge / discharge cycles were measured in the electrochromic elements according to the examples and comparative examples.
[0255] division Coloring speed (seconds) Charge / Discharge Recovery Example 1 62 20000 Example 2 46 19500 Example 3 31 20000 Example 4 23 19900 Example 5 15 20000 Comparative example 180 19800
[0256] As described in Table 2 above, the electrochromic element according to the examples had improved durability and coloring speed. Explanation of the symbols
[0257] First substrate (100) Second substrate (200) 1st transparent electrode (300) 2nd transparent electrode (400) First discoloration layer (500) Second discoloration layer (600) lithium-rich layer (700) electrolyte layer (800)
Claims
Claim 1 An electrochromic device comprising: a first substrate; a first transparent electrode disposed on the first substrate; a first photochromic layer disposed on the first transparent electrode; an electrolyte layer disposed on the first photochromic layer; a second photochromic layer disposed on the electrolyte layer; a second transparent electrode disposed on the second photochromic layer; a second substrate disposed on the second transparent electrode; and a lithium-rich layer disposed adjacently below the second photochromic layer and containing lithium at a higher concentration than the second photochromic layer, wherein the concentration of lithium in the second photochromic layer becomes progressively smaller as it approaches the second transparent electrode from the lithium-rich layer. Claim 2 delete Claim 3 An electrochromic device comprising: a first substrate; a first transparent electrode disposed on the first substrate; a first color-changing layer disposed on the first transparent electrode; an electrolyte layer disposed on the first color-changing layer; a second color-changing layer disposed on the electrolyte layer; a second transparent electrode disposed on the second color-changing layer; a second substrate disposed on the second transparent electrode; and a lithium-rich layer disposed adjacently below the second color-changing layer and containing lithium at a higher concentration than the second color-changing layer, wherein the lithium-rich layer contains lithium hydroxide. Claim 4 In claim 1, the first substrate and the second substrate are flexible electrochromic elements. Claim 5 The electrochromic device according to claim 1, wherein the lithium-rich layer has a thickness of 10 nm to 1000 nm. Claim 6 In claim 3, the electrochromic element wherein the first color-changing layer comprises tungsten oxide and the second color-changing layer comprises nickel oxide. Claim 7 A method for manufacturing an electrochromic device comprising: a step of preparing a first laminate including a first substrate, a first transparent electrode on the first substrate, and a first color-changing layer on the first transparent electrode; a step of preparing a second laminate including a second substrate, a second transparent electrode on the second substrate, a second color-changing layer on the second transparent electrode, and a lithium-rich layer on the second color-changing layer; a step of bonding the first laminate and the second laminate through an electrolyte layer, wherein the lithium-rich layer contains lithium at a higher concentration than the second color-changing layer, and the step of preparing the second laminate includes a step of coating a lithium hydrate on the second color-changing layer. Claim 8 delete Claim 9 A method for manufacturing an electrochromic device according to claim 7, wherein the step of preparing the second laminate further includes the step of heat-treating the lithium hydrate. Claim 10 A method for manufacturing an electrochromic device according to claim 9, wherein the concentration of lithium in the second chromogenic layer becomes progressively smaller as it approaches the second transparent electrode from the lithium-rich layer. Claim 11 A window device comprising: a frame; a window mounted on the frame; and an electrochromic element disposed in the window, wherein the electrochromic element comprises: a first substrate; a first transparent electrode disposed on the first substrate; a first color-changing layer disposed on the first transparent electrode; an electrolyte layer disposed on the first color-changing layer; a second color-changing layer disposed on the electrolyte layer; a second transparent electrode disposed on the second color-changing layer; a second substrate disposed on the second transparent electrode; and a lithium-rich layer disposed adjacent to the second color-changing layer and containing lithium at a higher concentration than the second color-changing layer, wherein the concentration of lithium in the second color-changing layer becomes progressively smaller as it approaches the second transparent electrode from the lithium-rich layer.
Citation Information
Patent Citations
Electrochromic element having improved ion conductor layer
JP2007108750A
Electrochromic device and manufacturing method thereof
KR1020030072123A
Electrochromatic device
KR1020170071681A
Electrochromic device
KR1020240020434A